Letter - Max Winter Limited; Hunt, E. D.
1940-01-08 038-0051-002 BRITISH YOUTH PEACE ASSEMBLY RELIEF AND REFUGEE COUNCIL SPANISH YOUTH COMMITTEE 15, GREAT JAMES STREET, LONDON, W.C.1 Holborn 4876 8 Jan. 1940 The Secretary, The International Solidarity Fund, Transport House, Smith Square, S.W.1. Dear Sir, I am sending you enclosed a letter received by my committee from Mr. Fred Winter, 101/2 Hatton Garden E.C.1. Unfortunately my Committee are in no position to help Senor Santiago Gallut Calvo and in view of his record I am sending the letter to you for your attention. Yours faithfully, E.D. Hunt. General Secretary. 292/946/38/51(II)